Research-Based Educational Innovation In The Development of Excellent Madrasah - Thoyib, Muhammad; Djohan, M. Widda; Rahmawati, Ryan (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2024)
This research is motivated by the existence of competition for educational institutions that are not paid attention to, which is caused by the lack of innovation by the madrasah head in determining strategies to improve the quality of education, causing the low quality and achievements obtained by the educational institution itself. Thus, a quality madrasah is certainly a madrasah that is able to produce outputs that are in accordance with market needs that can compete in various competitive eras. This study aims to describe research-based madrasah innovations carried out by madrasah stakeholders for the advancement of education. To answer this research, researchers used a phenomenological qualitative approach, with a case study research type. Data collection techniques include indepth interview, observation and documentation, besides using 3 approaches to data validity, namely extended observation, increasing persistence and data triangulation. Based on the results of study showed the conclusion that MAN 2 Kudus Central Java has a Research-Based Madrasah Program Team which is tasked with enriching creative ideas and reflecting on creative ideas about research issues by involving teachers, and researcher partnering (university researchers), through madrasah forums researching innovations at the beginning of each new school year and evaluating creative ideas by its team as part of integrated success efforts, both at national and international levels. The implications of these activities are material implications, which include the realization of commercial research products such as malaria drugs that can be mass produced, while non-material implications include the interest of the community of education service users which is increasing every year.